Potensi, Preferensi dan Perilaku Masyarakat Muslim Surabaya terhadap Wakaf Tunai sebagai Instrumen Pembiayaan Pembangunan - Fatma, Fatma (OECONOMICUS Journal of Economics, 2018)
Cash waqf in Indonesia has a great potential to be explored and developed into a solution in order to empower the people's economy. To that end, the purpose of this study is to provide information about the potential development of cash waqf based on the analysis of the potential of demographic, economic and social values. The study also analyzes how patterns of preferences and behaviors the community against cash waqf. Respondents used in this research is the 349 moslem community at Surabaya. Analytical techniques descriptive analysis is used. The results showed the potential cash waqf moslem society of Surabaya are very high based on indicators of demographic, economic and social values. Patterns of community preference in choosing cash waqf is based on consideration of the relative advantages, information disclosure, compatibility, complexity and triability. The fulfillment of such preference indicator against the formation of the moslem society of Surabaya positive behaviors that are ready to accept cash waqf in the concept level and run it in the practice level